2004
DOI: 10.1271/bbb.68.2360
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Farnesyl Diphosphate Synthase from the Rubber-Producing MushroomLactarius chrysorrheus

Abstract: Farnesyl diphosphate is involved in rubber biosynthesis as an initiating substrate for both polyprenol and mushroom rubber. So far, we have isolated the cDNA of a farnesyl diphosphate synthase (FPS) for the first time from a rare rubber-producing mushroom, Lactarius chrysorrheus, by the degenerate RT-PCR technique based on sequence information of FPS genes from fungi and yeasts. The open reading frame was clarified to encode a protein of 381 amino acid residues with a calculated molecular weight of 42.9 kDa. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…However, there has not been any reported activity of TbFPPS or TcFPPS with FPP. FPPS from the rubber-producing mushroom Lactarius chrysorrheus has been shown to be unable to form products with FPP as the substrate (48), and data from the Comprehensive Enzyme Information System (http://www.brenda-enzymes.org/) indicate that only DMAPP and GPP are substrates for FPPS enzymes from over 20 different species. However, FPPS enzymes from a number of parasitic protozoa, including Toxoplasma gondii (44), Plasmodium vivax (49), and Cryptosporidium parvum (50), were recently shown to be "bifunctional" prenyl synthases that are capable of accepting DMAPP, GPP, and FPP as substrates to produce FPP and GGPP, as well as, in some cases, products with even longer chains.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has not been any reported activity of TbFPPS or TcFPPS with FPP. FPPS from the rubber-producing mushroom Lactarius chrysorrheus has been shown to be unable to form products with FPP as the substrate (48), and data from the Comprehensive Enzyme Information System (http://www.brenda-enzymes.org/) indicate that only DMAPP and GPP are substrates for FPPS enzymes from over 20 different species. However, FPPS enzymes from a number of parasitic protozoa, including Toxoplasma gondii (44), Plasmodium vivax (49), and Cryptosporidium parvum (50), were recently shown to be "bifunctional" prenyl synthases that are capable of accepting DMAPP, GPP, and FPP as substrates to produce FPP and GGPP, as well as, in some cases, products with even longer chains.…”
Section: Discussionmentioning
confidence: 99%
“…An aliquot of the extracted hexane phase was then counted using a scintillation counter. In order to analyze the radioactive reaction products, enzymatic reactions were conducted in accordance with the method described by Mekkriengkrai et al (2004). The prenyl diphosphate products were extracted with 1-butanol saturated with water and then treated with potato acid phosphatase at 37 ºC overnight to hydrolyze the diphosphate moiety.…”
Section: Pgfps Expression and Fps Activity In E Colimentioning
confidence: 99%
“…Relative transcript levels of the G. lucidum FPS gene were determined by competitive PCR. 15,16) Total RNA was extracted from different G. lucidum developmental stages, including primordia and mycelial samples (10,12,14,16,18, and 20 d old), and an additional DNA digestion step was included (RNase Free DNase I, Takara, Dalian, China). Then aliquots of total RNA (1 mg) were reverse-transcribed to cDNA with a PrimeScriptÔ 1st Strand cDNA Synthesis Kit (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%
“…FPS genes and cDNAs were first characterized in vertebrates and Saccharomyces cerevisiae, 6) and more recently in many other species, including Arabidopsis thaliana, 7) maize, 8) rice, 9) Lactarius chrysorrheus, 10) dipteran, 11) and Schizosaccharomyces pombe. 12) Comparisons of the amino acid sequences of FPS, ranging from bacteria to higher eukaryotes, have shown that all the FPS known so far contain four distinct regions with high similarity at the amino acid level, two of which are present in all polyprenyl diphosphate synthases.…”
mentioning
confidence: 99%